Management and Outcome of Scabies in Primary Health Care in Low Income Countries: A Comprehensive Systematic Review - Yulianto, Ronald; Gunawan, Ellen Aristika (The International Journal of Medical Science and Health Research, 2024)
Background: Scabies is a highly contagious ectoparasitic skin infestation caused by Sarcoptes scabiei var. hominis. With a global prevalence of 204 million, scabies poses a remarkable burden on both infected individuals and on the healthcare system regardless of the socioeconomic standard of the respective country. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Topical treatment with permethrin cream (5%) is considered as the gold standard, leading to a cure in most of the cases.